The Effect of Taxpayer Knowledge, Taxpayer Awareness, and Service Quality on Motor Vehicle Taxpayer Compliance in Sidoarjo Regency During the Covid-19 Pandemic: Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kabupaten Sidoarjo Pada Masa Pandemi Covid-19 - Wulansari, Ema Dwi; Dewi, Santi Rahma (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine Taxpayer Knowledge, Taxpayer Awareness and Service Quality Against Motor Vehicle Taxpayer Compliance in Sidoarjo Regency during the Covid-19 Pandemic. This study uses primary data, namely questionnaires distributed to 50 respondents using random sampling technique as a sampling technique. The population of this study were residents of the Jabaran village of Kapas Melati Hamlet who used motorized vehicles. The data analysis technique used is descriptive statistical analysis, validity test, reliability test, multiple linear regression test, coefficient of determination test and t test using SPSS. v.25 in data processing. The results of this study indicate that during the Covid-19 pandemic in Sidoarjo Regency, taxpayer knowledge has a significant effect on motor vehicle taxpayer compliance, taxpayer awareness has a significant effect on motor vehicle taxpayer compliance, and service quality has a significant effect on motor vehicle taxpayer compliance.